2002
DOI: 10.1088/0953-8984/14/8/309
|View full text |Cite
|
Sign up to set email alerts
|

Gap states in a-SiC from optical measurements and band structure models

Abstract: Undoped and boron-doped a-Si 1−x C x :H, for x ≈ 0.5, films have been prepared by means of plasma-enhanced chemical-vapour deposition using methyltrichlorosilane.The optical absorption spectra of these films demonstrate three characteristic peaks at about 1.6, 2.0 and 2.5 eV consistent with other experimental measurements. To explain the observed peculiarities of the spectra, the atomic and electronic structures of a-SiC have been investigated using both molecular dynamics simulations based on an empirical pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…3 one can suppose that they result from the superposition of various absorption bands so as to make the characteristic three-stage spectrum. Indeed, Ivashchenko et al 9 have shown a theoretical approach of the absorption coefficient of a-Si x C 1−x alloys that leaded to an absorption spectra like ours. According to these authors, we have calculated the absorption coefficient of a material having three absorption peaks within the gap.…”
Section: Optical Study Of Disorder and Defects In Hydrogenated Amorphsupporting
confidence: 59%
See 1 more Smart Citation
“…3 one can suppose that they result from the superposition of various absorption bands so as to make the characteristic three-stage spectrum. Indeed, Ivashchenko et al 9 have shown a theoretical approach of the absorption coefficient of a-Si x C 1−x alloys that leaded to an absorption spectra like ours. According to these authors, we have calculated the absorption coefficient of a material having three absorption peaks within the gap.…”
Section: Optical Study Of Disorder and Defects In Hydrogenated Amorphsupporting
confidence: 59%
“…8 On the other hand, it has been proposed that various defect bands can be present in the gap of a-SiC:H alloys, resulting in a poor definition of the otherwise exponential absorption edge. 9 In this letter, we present data on the absorption coefa͒ Author to whom correspondence should be addressed; electronic mail: roca@poly.polytechnique.fr Hydrogenated amorphous silicon-carbon alloys ͑a-SiC:H͒ were deposited at 200°C on 1737 Corning glass in a capacitively coupled RF glow discharge reactor consisting of a cylindrical vessel of 11 cm diameter and an interelectrode distance of 2.5 cm. The silane, methane and hydrogen ͑SiH 4 -CH 4 -H 2 ͒ gas mixtures were dissociated with an rf power of 20 W under a total pressure of 3500 mTorr.…”
Section: Optical Study Of Disorder and Defects In Hydrogenated Amorphmentioning
confidence: 99%
“…The intensity of PL manifests the magnitude of DOS of defects. Multi-peak feature of PL spectra reflects the multi-peak distribution of DOS in band gap [19]. Furthermore, with the increasing carbon concentration, thereby optical band gap E G , the exponential absorption segment (corresponding to conduction band tail or Urbach edge) becomes broad [20,21].…”
Section: Ir Transmittancementioning
confidence: 99%
“…Thus, to investigate the electronic properties of semiconductor quantum dots, we employed the sp 3 s * TB scheme. The atomic-distance-dependent TB parameters proposed by Ivashchenko et al were used for the Si-Si, Si-C, and C-C [47,48]. The form of the pairwise potential and the parameters relating to the Si-H and C-H pairs were newly determined for our TB-MD simulations based on the previous studies [49][50][51][52] 4 .…”
Section: Tb Scheme and Models Of Semiconductor Quantum Dots For MD Simentioning
confidence: 99%
“…In the TB model proposed by Ivashchenko et al, [47,48] the matrix elements of H TB are expressed using the atomic-distance-dependent forms, and the overlap integrals of wave functions are approximated by delta functions, .…”
Section: Appendix Amentioning
confidence: 99%